Peran Etika Administrasi dalam Meningkatkan Profesionalisme Pelayanan Publik di Dinas Sosial Pemprov Sumatera Barat - Wulandari, Miken; Yunita, Yunita; Welni, Afrina; Putra, Randhy Wilyan; Hanoselina, Yulia; Helmi, Rahmadhona Fitri (CV. ITTC INDONESIA, 2024)
Title: The Impact of Administrative Ethics on the Effectiveness of Public Service at the Social Service Office of West Sumatra Province This study explores the influence of administrative ethics on the effectiveness of public services at the Social Service Office of West Sumatra Province. Employing a mixed-methods approach, both qualitative and quantitative data were collected through surveys and interviews with employees and service users. The findings reveal that adherence to ethical standards significantly enhances the efficiency and quality of public services. Key ethical principles such as transparency, accountability, and fairness were found to be crucial in shaping positive service outcomes. The study highlights that fostering a strong ethical culture within the administrative framework can lead to improved public satisfaction and operational effectiveness. Recommendations for policy improvements are also discussed to support better service delivery.